Nutritional and supplementation strategies to prevent and attenuate exercise-induced muscle damage: a brief review - Harty, P. S.; Cottet, M. L.; Malloy, J. K.; Kerksick, C. M. (Sports Medicine, 2019)
Exercise-induced muscle damage (EIMD) is typically caused by unaccustomed exercise and results in pain, soreness, inflammation, and reduced muscle function. These negative outcomes may cause discomfort and impair subsequent athletic performance or training quality, particularly in individuals who have limited time to recover between training sessions or competitions. In recent years, a multitude of techniques including massage, cryotherapy, and stretching have been employed to combat the signs and symptoms of EIMD, with mixed results. Likewise, many varied nutritional and supplementation interventions intended to treat EIMD-related outcomes have gained prominence in the literature. To date, several review articles have been published that explore the many recovery strategies purported to minimize indirect markers of muscle damage. However, these articles are very limited from a nutritional standpoint. Thus, the purpose of this review is to briefly and comprehensively summarize many of these strategies that have been shown to positively influence the recovery process after damaging exercise. These strategies have been organized into the following sections based on nutrient source: fruits and fruit-derived supplements, vegetables and plant-derived supplements, herbs and herbal supplements, amino acid and protein supplements, vitamin supplements, and other supplements. Abstract from author